HUBUNGAN ANTARA KOMUNIKASI INTERPERSONAL MAHASISWA DAN DOSEN DENGAN MOTIVASI BELAJAR - Abigail Tandilangi; Cherlyn Regina Rompis (Klabat Journal of Nursing, 2022)
Learning is an activity carried out by students so that there is a change from not knowing to know. In the learning process, students must have motivation in themselves to be able to encourage students to do learning activities. In the learning process, communication must be built between students and lecturers so that learning activities can be well established. The purpose of this study was to determine the relationship between interpersonal communication of students and lecturers with learning motivation for level I and II students at a private university in North Sulawesi. The research design used is quantitative correlation with a cross-sectional approach. The sample of this study amounted to 148 people who were taken using Purposive Sampling technique. Results of this study indicate that the description of interpersonal communication is included in the poor category (53.4%) and the description of learning motivation is included in the high category (50.7%). The results of the Spearmen's Rank/Rho test show p value = 0.000 <0.05, meaning that there is a significant relationship between student and lecturer interpersonal communication and learning motivation. Recommendations for level I and II students to be active by asking questions and opinions during teaching and learning activities and to establish good communication with lecturers. KEYWORDS: Communication, Interpersonal, Learning Motivation KEYWORDS: Communication, Interpersonal, Learning Motivation Belajar merupakan kegiatan yang dilakukan oleh mahasiswa sehingga terjadi perubahan dari yang tidak tahu menjadi tahu. Dalam proses belajar mahasiswa harus memiliki motivasi dalam dirinya untuk dapat mendorong melakukan kegiatan belajar. Dalam proses pembelajaran pentingnya terjalin komunikasi yang baik antara mahasisiwa dan dosen agar kegiatan belajar dapat berjalan dengan baik. Tujuan dari penelitian ini untuk mengetahui hubungan antara komuniksi interpersonal mahasiswa dan dosen dengan motivasi belajar pada mahasisiwa tingkat I dan II pada salah satu universitas swasta di Sulawesi Utara. Desain penelitian yang digunakan adalah kuantitatif korelasi dengan pendekatan Cross-Sectional. Sampel penelitian berjumlah 148 orang yang diambil menggunakan teknik Purposive Sampling. Hasil dari penelitian menunjukkan gambaran komunikasi interpersonal termasuk dalam kategori kurang baik (53,4%) dan gambaran motivasi belajar termasuk dalam kategori tinggi (50,7%). Hasil uji Spearmen’s Rank/Rho menunjukkan p value = 0,000<0,05 artinya ada hubungan yang signifikan antara komunikasi interpersonal mahasiswa dan dosen dengan motivasi belajar. Rekomendasi bagi mahasisiwa tingkat I dan II untuk dapat aktif memberikan pertanyaan dan pendapat selama mengikuti kegiatan belajar-mengajar serta dapat menjalin komunikasi yang baik dengan dosen. KATA KUNCI: Komunikasi, Interpersonal, Motivasi Belajar